Evaluation Of The Use Of Antidiabetic Drugs For Geriatric Patients With Type 2 Diabetes Mellitus In Outpatient Care At Fatmawati Hospital, South Jakarta In 2023. - Maria Melda Mola; Agus Purwanggana; Ahmad Subhan; Anak Agung Arie Widyastuti (Jurnal Farmasi Klinik Best Practice, 2025)
Diabetes mellitus is a non-communicable disease that has a large prevalence and is increasing every year in Indonesia. Evaluation of the use of antidiabetic drugs aims to ensure that patients with diabetes mellitus use antidiabetic drugs appropriately. This study is an observational study with retrospective descriptive analysis using patient medical record data. In this study, an evaluation was carried out on outpatient type 2 diabetes mellitus geriatric patients with a total of 200 patients based on PERKENI in 2021 with an accuracy standard of 100%. Evaluation of drug use is divided into 3 parameters, namely the right indication, the right drug, and the right dose. Based on the analysis of demographic data, most patients are at the age of 60-69 years and are female. Based on clinical data analysis, patients with the highest level of diabetes are type 2 diabetes mellitus without comorbidities or complications. Based on the results of the evaluation, the most common pattern of drug use is monotherapy. Based on the evaluation results, the right indication was obtained for 200 patients (100%), the right drug for 178 patients (89%) and the right dose for 199 patients (99.5%). Based on Hemoglobin A1c, FBS, PGB and RBGS, 188 patients (94%) had controlled diabetes. In this study, it can be concluded that there are still discrepancies in the use of antidiabetic drugs in outpatient type 2 diabetes mellitus geriatric patients at Fatmawati General Hospital in 2023.